2004
DOI: 10.1016/j.physd.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Soliton-like phenomena in one-dimensional cross-diffusion systems: a predator–prey pursuit and evasion example

Abstract: We have studied properties of nonlinear waves in a mathematical model of a predator-prey system with pursuit and evasion. We demonstrate a new type of propagating wave in this system. The mechanism of propagation of these waves essentially depends on the "taxis", represented by nonlinear "cross-diffusion" terms in the mathematical formulation. We have shown that the dependence of the velocity of wave propagation on the taxis has two distinct forms, "parabolic" and "linear". Transition from one form to the othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
1
41
0
4
Order By: Relevance
“…Examples of systems that exhibit cross-diffusion include strong electrolytes, [23][24][25] micelles, 26,27 or microemulsions, 28 and systems containing molecules of significantly different sizes, for example protein-salt. [29][30][31] Similar phenomena also occur in biological systems, but since the transport process is driven by an input of energy, as, for example, in bacterial chemotaxis [32][33][34] or in predator-prey systems, [35][36][37][38] these are not true diffusion processes. Nonetheless, the mathematical description of biological or ecological cross-diffusion is the same as in physicochemical systems, as we discuss below.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of systems that exhibit cross-diffusion include strong electrolytes, [23][24][25] micelles, 26,27 or microemulsions, 28 and systems containing molecules of significantly different sizes, for example protein-salt. [29][30][31] Similar phenomena also occur in biological systems, but since the transport process is driven by an input of energy, as, for example, in bacterial chemotaxis [32][33][34] or in predator-prey systems, [35][36][37][38] these are not true diffusion processes. Nonetheless, the mathematical description of biological or ecological cross-diffusion is the same as in physicochemical systems, as we discuss below.…”
Section: Introductionmentioning
confidence: 99%
“…The approximation of the taxis term is an "upwind" explicit scheme [25] which is frequently used for cross-diffusion systems (e.g., [26]). More precisely, …”
Section: Appendixmentioning
confidence: 99%
“…Citing from a recent instance, we would like to consider here a pursuit-evasion model investigated by Tsyganov and co-authors [40,41,39,38]:…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the local kinetics of model (2.2) consists of logistic reproduction of prey, Holling type-III trophic function, and constant rate of predator mortality. The authors have demonstrated that the model has very interesting spatially heterogeneous regimes including solitonic [40,41] and spiral waves [38]. Basing on the mathematical models of type (2.2) and experimental work with bacterial populations, such waves in excitable cross-diffusion systems have been identified as a new class of nonlinear waves [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation